FAKTOR TERKAIT GANGGUAN FUNGSI PARU PADA PEKERJA WANITA DI PABRIK ROKOK PRAOE LAJAR SEMARANG, JAWA TENGAH - Diyah Putri Permata; Budiono Budiono; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Occupational lung disease (PPAK) is a disease or lung damage caused by dust, vapors or hazardous gas that workers inhale at work. The incidence of PPAK affects the lung capacity by indicating a recurrent, obstructive, or combined disorder. The rate of illness in Indonesia reaches 70% of workers exposed to high dust. This study aims to analyze factors related to lung function disorder of female workers of cigarette factory Praoe Lajar Semarang, Central Java. This type of observational research with Cross Sectional approach using 36 samples. The research instrument in this research is Questionnaire, Personal dust sampler to measure the dust personal and Spirometer to measure lung function. Univariate and bivariate data analysis. The results showed that 55,6% of workers had impaired lung function (41,7% restrictive, 8.3% obstructive, and 5,6% mixed restrictive-obstructive) and the variables that proved to be related factors and as risk factors for lung function impairment were inhaled exposure (p = 0,001; PR = 3,000; 95% CI = 1,704-5,283) and length of service (p = 0,024; PR = 2,8; 95% CI =  1,029–7,803), variable not proven as related factor but become risk factor to incidence of lung function disorder is personal age (p= 0,229; PR= 1,696; 95% CI=  0,801-3,588), and nutritional status(p= 0,793; PR= 1,200; 95% CI=  0,654-2,201). The conclusion of this research is the risk factor related to the incidence pulmonary disorder in the cigarette factory workers Praoe Lajar Semarang is exposure to inhaled dust and working period.